2020
DOI: 10.1097/phm.0000000000001349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Exercise Intensities on Headache

Abstract: The benefits of the regular exercise on quality of life of individuals living with a headache are well known. However, whether the benefits of the exercise training on headache parameters (i.e., intensity, frequency, and pain duration) occur in an intensity-dependent fashion remains unknown. Objective The aim of the study was to investigate the effects of different exercise intensities on headache parameters. Design A systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
1
17
0
3
Order By: Relevance
“…In agreement with our findings, a review article revealed that aerobic exercise can alleviate the duration of migraine headaches and also somewhat decrease the incidence of these headaches [33]. In another similar study, a beneficial effect of exercise on primary headaches including migraine and tension-type headaches and also a decrease in the use of headache-related medications were reported [34]. In a study on 22,397 adults, a sedentary lifestyle was associated with an increased risk of non-migraine headaches [15].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings, a review article revealed that aerobic exercise can alleviate the duration of migraine headaches and also somewhat decrease the incidence of these headaches [33]. In another similar study, a beneficial effect of exercise on primary headaches including migraine and tension-type headaches and also a decrease in the use of headache-related medications were reported [34]. In a study on 22,397 adults, a sedentary lifestyle was associated with an increased risk of non-migraine headaches [15].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, a growing body of experimental and treatment outcome research points to therapeutic exposure to triggers as a promising line of migraine intervention 31,32 . Although recent systematic reviews have supported the prophylactic value of exercise, 33,34 much work remains in determining the optimal parameters of such PA (eg, intensity, duration) 34 . Future studies should investigate further the fear‐avoidance properties of salient migraine stimuli (eg, light, sound, and PA) and their role in the progression of disability.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the minimal side effects of therapeutic exercise, patients with migraine should be encouraged to practice physical exercise; but with proper intensity, frequency, and duration, to achieve the most beneficial clinical outcomes. In fact, a recent meta-analysis concluded that data on the best type of exercise, intensity, and dosage for the management of headaches are still lacking [75]. Another topic for determining relevance is adherence and patient' satisfaction.…”
Section: Scientific Evidence Of Exercise Interventions For Headachesmentioning
confidence: 99%